2015
DOI: 10.1016/j.drugpo.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory qualitative assessment of self-reported treatment outcomes and satisfaction among patients accessing an innovative voluntary drug treatment centre in Malaysia

Abstract: Background In Malaysia, compulsory drug detention centres (CDDCs) hold suspected drug users for two years without adjudication. Acute detoxification without healthcare access has been documented. CDDCs are criticized globally due to ineffectiveness in treating addiction and human rights violations. In response, the Malaysian government began transitioning these facilities into voluntary drug treatment centres known as “Cure and Care” (C&C) centres that embrace a holistic treatment-based approach to drug addict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…HIV risk assessments of drug users in Malaysia have almost exclusively focused on men in community (5560) and criminal justice (33, 37, 38, 61–64) settings. Indeed, even in Malaysia’s largest study of PWID (N=460), which used respondent-driven sampling, only 17 (3.7%) women were successfully recruited despite increased recruitment incentives (42, 65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV risk assessments of drug users in Malaysia have almost exclusively focused on men in community (5560) and criminal justice (33, 37, 38, 61–64) settings. Indeed, even in Malaysia’s largest study of PWID (N=460), which used respondent-driven sampling, only 17 (3.7%) women were successfully recruited despite increased recruitment incentives (42, 65).…”
Section: Discussionmentioning
confidence: 99%
“…Since medication-assisted therapies are not routinely available for the treatment of ATS-use disorders (5), counseling-based strategies are the mainstay for treating amphetamine addiction. Recently in Malaysia, there has been a transformation from CDDCs to integrated voluntary drug treatment programs, including treatment for ATS (57, 60), that could play a role in engaging women who use drugs, including ATS, especially if that care is sensitive to the unique health needs of women.…”
Section: Discussionmentioning
confidence: 99%
“…429 A qualitative study indicated that patients appreciated the range of activities offered in the new services, including the stabilizing effect of OST, psychosocial support from staff and peers, and links to other health services. 431 …”
Section: A Better Way For Drug Policy? Learning From Selected Experiementioning
confidence: 99%
“…Degenhardt, et al, 2013a). There are currently 59 Cure and Care centers operated under National Anti-Drug Agency (NADA-AADK) which are client-friendly (Ghani, et al, 2014; Ngadiman, 2014). Furthermore, AADK has plans to convert 18 of the 28 CDDCs into voluntary treatment centers by 2015 (Kaur, 2013).…”
Section: Discussionmentioning
confidence: 99%